Cost of Treating Maternal Complications and Associated Factors in Mekelle General Hospital, Northern Ethiopia - Abadi T; Mebratie AD (Dove Medical Press, 2021)
Teamir Abadi,1 Anagaw Derseh Mebratie2 1Health Bureau Health Care Financing Reform Case Team, Tigray Regional Health Bureau, Mekelle, Ethiopia; 2School of Public Health, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Teamir AbadiTigray Regional Health Bureau, Mekelle, EthiopiaTel +251914423809Fax +251344408830Email teamirabadi2@gmail.comBackground: The government of Ethiopia introduced an exemption policy that guarantees free maternal healthcare services from public providers. This policy aims to ensure financial protection and enhance utilization of services especially for low-income people. However, patients in most cases incur health expenditure when seeking health care. This paper aims to assess direct and indirect medical costs of treating maternal complications and associated factors at a public hospital in Northern Ethiopia.Methods: An institution-based cross-sectional study design was carried on 267 mothers with complications. A multivariate linear regression model at 5% level of significance was used to analyze factors driving the outcome.Results: The median cost was more than seven times the monthly minimum wage, and this may cause severe financial consequences for the poor. Direct medical costs accounted for the major share (68%) of total cost, and this was mainly driven by lack of diagnostic services at public facilities and paying for private providers. Expenditure for treatment of maternal complications is positively associated with income, absence from work, travel time to the facility and being diagnosed at a private facility.Conclusion: The overall evidence in this study poses a concern about the context in which fee exemption reforms are being implemented.Keywords: maternal complications, treatment, direct and indirect costs, Mekelle, Ethiopia